Non-suicidal self-injury and emotion regulation: a review on facial emotion recognition and facial mimicry - In-Albon, Tina (BioMed Central, 2013)
Non-suicidal self-injury (NSSI) is an increasingly prevalent, clinically significant behavior in adolescents and can be associated with serious consequences for the afflicted person. Emotion regulation is considered its most frequent function. Because the symptoms of NSSI are common and cause impairment, it will be included in Section 3 disorders as a new disorder in the revised Diagnostic and Statistical Manual of Mental Disorders (DSM-5). So far, research has been conducted mostly with patients with borderline personality disorder (BPD) showing self-injurious behavior. Therefore, for this review the current state of research regarding emotion regulation, NSSI, and BPD in adolescents is presented. In particular, the authors focus on studies on facial emotion recognition and facial mimicry, as social interaction difficulties might be a result of not recognizing emotions in facial expressions and inadequate facial mimicry. Although clinical trials investigating the efficacy of psychological treatments for NSSI among adolescents are lacking, especially those targeting the capacity to cope with emotions, clinical implications of the improvement in implicit and explicit emotion regulation in the treatment of NSSI is discussed. Given the impact of emotion regulation skills on the effectiveness of psychotherapy, neurobiological and psychophysiological outcome variables should be included in clinical trials.